Studi Komposisi Media Tumbuh dan Bahan Setek Pada Produksi Benih Klonal Kopi Robusta - Nur Kholis Firdaus; Dibyo Pranowo; Edi Wardiana (Pusat Penelitian dan Pengembangan Perkebunan, 2021)
The growth media composition and cuttings material is considered one of the determining factors for a successful Robusta coffee plant propagation by cuttings. Information on the growth media composition and the ideal cutting material for Robusta coffee needs to be improved. The research was conducted at the Pakuwon Experimental Station and Integrated Laboratory, Balittri, Sukabumi, from October 2020 to January 2021. The study aimed to investigate the effect of growth media composition and number of internodes on the growth of cuttings in three clones of Robusta coffee. The study was designed in a split-split plot with 2 replications. The main plot factor was 3 clones of Robusta coffee (BP 939, SA 203, and BP 308), the split plot factor was 5 compositions of growth media: sand, sand+chicken manure (1:1), sand+soil (1:1), soil+chicken manure (1:1), and sand+soil+chicken manure (1:1:1), and the split-split plot factor was the number of internodes (1 and 2 internodes). Variables observed were the percentage of survived, sprouted, and rooted cuttings, number and length of primary roots, and number of shoots, internodes and leaves. The results showed that sand and sand+soil (1:1) were the best media for root formations. For the growth of number and length of primary roots, the sand+soil (1:1) media was a more suitable for BP 939 and SA 203, while sand media was suitable for BP 308. Other result showed that two-internodes cuttings proved to be better in shoot, internode, and leaf growth than single-internode cuttings.